THE IMPORTANCE OF PRODUCTION PLANNING AND CONTROL (PCP) FOR THE DEVELOPMENT OF CURRENT INDUSTRIES - Bugor, Francelini Bugor; Lucca Filho , João de (Revista Interface Tecnológica, 2021)
This article demonstrates the importance of using Production Planning, Programming and Control (PPCP) in organizations, as, over time, society has become concerned with the efficient use of resources and integrated with the environment, minimizing waste as much as possible. Thus, new concepts and studies have been developed in industrial processes, among them, production systems and management functions are the most studied. Production Planning and Control (PCP) emerges as a tool that aims to control and plan the entire production system, allowing the organization to achieve more efficient production with the same inputs. This tool has become an essential activity for the industries, and as an activity it has become the area responsible for the management and monitoring of production activities, aiming to meet the demand of its consumers, and mainly obtaining the reduction of all costs related to the production process, such as labor, inputs and raw materials. Finally, the use of software tools to support decision making at all levels to control the entry and exit of materials and their real need was analyzed, through the detailed planning of daily activities related to the production process within an organization.